2021
DOI: 10.3390/nu13010275
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Properties of Natural Compounds in Cardiac Stem Cell Activation: Their Role in Myocardial Regeneration

Abstract: Cardiovascular diseases (CVDs), which include congenital heart disease, rhythm disorders, subclinical atherosclerosis, coronary heart disease, and many other cardiac disorders, cause about 30% of deaths globally; representing one of the main health problems worldwide. Among CVDs, ischemic heart diseases (IHDs) are one of the major causes of morbidity and mortality in the world. The onset of IHDs is essentially due to an unbalance between the metabolic demands of the myocardium and its supply of oxygen and nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 252 publications
(222 reference statements)
0
8
0
Order By: Relevance
“…Under these conditions, protective mechanisms that include the overexpression of endogenous antioxidant enzymes, UPR, and autophagic responses are activated with the aim of antagonizing the apoptotic cell death of myocardial cells [ 153 ]. Since BPF counteracts oxidative stress in in vitro and in vivo cardiotoxicity models [ 49 , 50 , 53 ], in addition to reverting mitochondrial dysfunction [ 94 , 148 , 153 ], it is likely to assume its protective role even in the early stages of diabetic cardiomyopathy, in cardiac dysfunction, and in countering the development of heart failure.…”
Section: Diabetic Cardiomyopathy and Bergamot Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, protective mechanisms that include the overexpression of endogenous antioxidant enzymes, UPR, and autophagic responses are activated with the aim of antagonizing the apoptotic cell death of myocardial cells [ 153 ]. Since BPF counteracts oxidative stress in in vitro and in vivo cardiotoxicity models [ 49 , 50 , 53 ], in addition to reverting mitochondrial dysfunction [ 94 , 148 , 153 ], it is likely to assume its protective role even in the early stages of diabetic cardiomyopathy, in cardiac dysfunction, and in countering the development of heart failure.…”
Section: Diabetic Cardiomyopathy and Bergamot Polyphenolsmentioning
confidence: 99%
“…To date, the protective effects of the main polyphenols contained in high concentration in bergamot are well-known. In particular, important beneficial effects on the nervous system [ 41 , 42 , 43 ], the mineralization of bones [ 44 ], the regulation of keratinocytes [ 45 ], the regulation of the metabolism [ 46 , 47 ], against adipose-tissue inflammation [ 48 ] and during myocardial regeneration [ 49 ] were reported. These protective effects of bergamot have been found in many of its formulations: extract (BE), juice (BJ), essential oil (BEO), and polyphenolic fraction (BPF).…”
Section: Introductionmentioning
confidence: 99%
“…These cell lines can differentiate into all somatic cells and can express cardiac-specific markers, such as GATA-4, GATA-2, and Nkx2.5, giving these cardiac cells mature electrophysiological function. Injection of iPSCs into patients, who have previously sustained a myocardial infarction, provides evidence of increased left ventricular function and cardiac contractility, with a decrease in cardiac remodeling [ 20 ]. Several cardiovascular diseases have been modeled with human iPSCs to date, including dilated cardiomyopathy, Brugada Syndrome, calcific aortic valve, and long-QT syndromes [ 21 ].…”
Section: Introduction To Stem Cellsmentioning
confidence: 99%
“…Recently, several studies have confirmed that plant derivate natural substances, whether of terrestrial or marine origin can reduce the incidence of different pathologies including neurodegenerative 10–14 , cancer and heart diseases 15 , 16 , chronic inflammation and arthritis 17 , 18 . Among several promising compounds, resveratrol (Res) is one of the most studied and best known for its potential as a therapeutic agent for neurodegenerative diseases 19–21 .…”
Section: Introductionmentioning
confidence: 99%